Who brings home the pork? Parties and the role of localness in committee assignments in mixed-member proportional systems. (September 2018) - Gschwend, Thomas; Zittel, Thomas
The assignment of seats to specialized standing committees is a most consequential choice in legislative contexts. Distributive theories of legislative organization suggest that electoral incentives to cultivate personal votes result in the self-selection of legislators to committees best suited to please their constituents and, thus, to secure reelection. However, these theories discard the partisan basis of European parliaments and therefore fail to adequately assess the politics of committee assignments in these particular contexts. This article aims to explore the significance of distributive theories for the German case in differentiated ways and on the basis of a new and rich data set including statistical data for five legislative terms (1983, 1987, 1998, 2005, and 2009). It argues that in partisan assemblies, political parties might develop an interest in distributive politics themselves and might assign distinct types of legislators to distinct committees to seek personal votes contingent upon distinct electoral incentives. Particularly, we argue that Germany's mixed proportional system provides incentives to parties to assign legislators with profound local roots to district committees best suited to please geographic constituents.